2019
DOI: 10.1002/pri.1803
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent validity and intratester reliability of the video‐based system for measuring gait poststroke

Abstract: Background and purposeSpatio‐temporal parameters are commonly used in gait assessment. Advanced tools provide valid and reliable data, considered very effective for physiotherapy intervention. However, these tools may be limited in clinical usage caused by complicated applicability, inaccessibility, and high cost. Therefore, a video‐based system is an alternative choice that is easy and affordable for the clinical setting. The purpose of the study was to evaluate the concurrent validity of the video‐based syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The platform was installed in the middle part of a 5 m walkway and was synchronized with a video camera (SYNCCam) placed in front of the participants to check walking patterns for each trial. The FDM platform is widely used for gait assessment in various neurological conditions and was used as a gold standard to another proposed tool [56][57][58][59]. To remove the effect of the acceleration and deceleration phases of walking, gait data were recorded from the middle part of the walkway.…”
Section: Methodsmentioning
confidence: 99%
“…The platform was installed in the middle part of a 5 m walkway and was synchronized with a video camera (SYNCCam) placed in front of the participants to check walking patterns for each trial. The FDM platform is widely used for gait assessment in various neurological conditions and was used as a gold standard to another proposed tool [56][57][58][59]. To remove the effect of the acceleration and deceleration phases of walking, gait data were recorded from the middle part of the walkway.…”
Section: Methodsmentioning
confidence: 99%
“…Temporo-spatial gait variables. Temporo-spatial gait variables were measured using a 2D motion analysis system which has been show to be valid and reliable by a previous study on 20 stroke survivors 31 . The validity of the system was evaluated by comparing with a standard gait system (Force Distribution Measurement, FDM), with strong correlations (r p = 0.94-0.99, p < 0.001) for all gait variables between the 2D motion analysis system and the FDM.…”
Section: Procedures Randomization and Blindingmentioning
confidence: 99%
“…Previous research has shown that stroke not only leads to mortality and disability but also significantly lowers quality of life. [28][29][30][31] Researchers have found that patients' QOL can decrease due to the presence of chronic conditions like viral infections, metabolic disorders, and cardiovascular disease. 32 The study includes measurements of a wide range of HRQoL, including general health, pain, social health, emotional well-being, energy, and physical function.…”
Section: Resultsmentioning
confidence: 99%